Management of Dysphagia Pre- and Postoperatively in a Case of Eagle's Syndrome. (17th March 2015) - Lewis, Vicki; Hoffman Ruddy, Bari; Lehman, Jeffrey; Silverman, Erin; Spector, Brian
Abstract : Eagle's syndrome (ES) is rare condition, most frequently described within the context of case study presentation. ES results from elongation of the styloid process, contributing to symptoms such as globus sensation in the throat, as well as pain localized to the ear, neck, face, or tongue. Additional symptoms can include hypersalivation, change in vocal quality, submandibular swelling, and dysphagia. This report discusses evaluation, diagnosis, and surgical intervention with respect to Eagle's Syndrome in a patient presenting with moderate-severe dysphagia.